Temiar religion, 1964-2012 enchantment, disenchantment and re-enchantment in Malaysia's uplands - Benjamin, Geoffrey (NUS Press, 2014)
The Temiars, a Mon-Khmer-speaking Orang Asli society living in the uplands of northern Peninsular Malaysia, have long attracted popular attention in the West for reports that ascribed to them the special psychotherapeutic known as 'Senoi Dreamwork'. However, the reality of Temiar religion and society, as studied and recorded by Geoffrey Benjamin over 50 years, is even more fascinating than that popular portrayal - which is shown to be based on a serious misrepresentation of Temiar practice. When Benjamin first lived in the isolated villages of the Temiars between 1964 and 1965, he encountered a people who lived by swidden farming supplemented by hunting and fishing. They practised their own unexportable, localised animistic religion in an area where the main religion of civilisation was formerly Mahayana Buddhism and is now Islam. Fifty years later, the Temiars have become much more embedded in broader Malaysian society, while retaining their distinctive way of life, including continuing involvement with their complex shamanic religion. Benjamin's ongoing fieldwork in the 1970s, 1990s and 2000s followed the Temiars through processes of religious dis-enchantment and re-enchantment, as they reacted in various ways to the advent of Baha'i, Islam and Christianity. Some Temiars even developed a new religion of their own. In addition to its rich ethnographic reportage, the book proposes a novel theory of religion and develops a deeply insightful account of the changing intellectual framework of anthropology over the past half-century.